2020
DOI: 10.1002/chem.202000155
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Interrogation to Crack the Case of O‐GlcNAc

Abstract: The O‐linked β‐N‐acetylglucosamine (O‐GlcNAc) modification, termed O‐GlcNAcylation, is an essential and dynamic post‐translational modification in cells. O‐GlcNAc transferase (OGT) installs this modification on serine and threonine residues, whereas O‐GlcNAcase (OGA) hydrolyzes it. O‐GlcNAc modifications are found on thousands of intracellular proteins involved in diverse biological processes. Dysregulation of O‐GlcNAcylation and O‐GlcNAc cycling enzymes has been detected in many diseases, including cancer, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 156 publications
(185 reference statements)
0
11
0
Order By: Relevance
“…Abundant studies have shown that the homeostasis of O-GlcNAc levels is related to the occurrence and development of many diseases, such as diabetes, neurodegenerative diseases, cancer, and some autoimmune diseases. Therefore, it exhibited a great significance for the detection and identification of O-GlcNAc glycosylated proteins ( Vocadlo, 2012 ; Chaiyawat et al, 2014 ; Worth et al, 2017 ; Hanover et al, 2018 ; Nagy et al, 2019 ; Estevez et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Abundant studies have shown that the homeostasis of O-GlcNAc levels is related to the occurrence and development of many diseases, such as diabetes, neurodegenerative diseases, cancer, and some autoimmune diseases. Therefore, it exhibited a great significance for the detection and identification of O-GlcNAc glycosylated proteins ( Vocadlo, 2012 ; Chaiyawat et al, 2014 ; Worth et al, 2017 ; Hanover et al, 2018 ; Nagy et al, 2019 ; Estevez et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, chemical immunology emerges as a fertile area in which novel chemical strategies can be developed and exploited to uncover new roles of O-GlcNAc in immunity. 265 In conclusion, as shown in this review, chemistry will certainly continue to be a key enabling tool in the O-GlcNAc field, providing new probes, strategies and synthetic solutions to address outstanding challenges in the study of this significant protein modification. Nonetheless, it will only be through a multi-and interdisciplinary approach combining chemical, biological and structural techniques that we, as a community, will succeed in the complex, multi-faceted mission of elucidating the mechanisms and functional consequences of O-GlcNAcylation.…”
Section: Discussionmentioning
confidence: 84%
“…Thus, chemical immunology emerges as a fertile area in which novel chemical strategies can be developed and exploited to uncover new roles of O -GlcNAc in immunity. 265 …”
Section: Discussionmentioning
confidence: 99%
“…There has been much progress in the development of specific and potent cell‐permeable inhibitors of O‐GlcNAc cycling enzymes, and this has helped to enhance our understanding of the structural, scaffolding, and catalytic functions of the enzymes. Since recent well‐reviewed papers have thoroughly covered the topics of the O‐GlcNAc‐processing enzymes [97] and their small molecular inhibitors, [23,98,99] this section focuses on recently reported chemical genetic strategies available for interrogating protein selective and/or site‐selective O‐GlcNAcylation.…”
Section: Chemical Genetic Strategies Available For Interrogating Selective Protein O‐glcnacylationmentioning
confidence: 99%
“…These unprecedented findings were aided by the development of novel strategies and engineered molecular tools and optimization of previous methods to dissect the molecular functions of O‐GlcNAc and its dynamic regulations. Since there are excellent reviews broadly covering various strategies and molecular tools used for the dissection of O‐GlcNAc functions, [22,23] this mini‐review specifically focuses in great depth on recent advances in strategies and tools being applied to the detection of O‐GlcNAcylation on cellular proteins as well as on individual proteins. Moreover chemical genetic strategies that are being used or are potentially usable in future studies for discovering protein‐ or site‐specific O‐GlcNAcylation in vivo are also discussed.…”
Section: Introductionmentioning
confidence: 99%